Convection in a differentially heated cavity with a conducting fin attached at the bottom and ceiling. (1st May 2022) - Liu, Yang; Zhang, Shuaikun
Highlights: The entire thermal boundary layer could transition to an oscillatory state due the convective instability above the fin. Horizontal flow rate across the cavity is enhanced by up to 175.3% in the early stage and up to 467.1% in the fully-developed stage. Heat transfer across the cavity is improved by up to 71.05% due to the presence of fins. A multi-plume flow behaviour that is similar to the Rayleigh-Bénard instability is identified above the fin. Abstract: The flow and heat transfer within a differentially heated convective cavity, whose bottom and ceiling are attached with a conducting thin fin, are investigated with numerical simulations in this study. Rayleigh number from 5 × 10 7 to 1.84 × 10 9, and fin length from 1/6 to 1/2 are examined and analysed. The numerical results demonstrate that plume flow, which is similar to the extensively studied Rayleigh-Bénard convection, separates intermittently from the horizontal thin fin and it subsequently causes strong oscillations in the entire vertical thermal boundary layer. It is also found that the Rayleigh number and fin length distinctly impact the origination and development of the plume flow, as well as the interaction between the plume and its downstream vertical boundary layer. The present simulation results demonstrate that the integral absolute horizontal velocity on the cavity centreline Q is remarkably enhanced by 175.3% in the early stage and it is improved by 467.1% in the fully-developed stage at Ra =1.84 × 10 9 and s  = 1/2. It is further revealed that heat transfer across the convective cavity increases with fin length and a maximum enhancement factor 71.05% is achieved at Ra =1.84 × 10 9 and s  = 1/2. Nevertheless, it also demonstrates that compared to the Nusselt number in a non-finned cavity, heat transfer through the heated sidewall is depressed in the present finned cavity owing to a lower temperature difference adjacent to the heated sidewall.